2007
DOI: 10.1111/j.1475-4754.2007.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

THE CHEMICAL COMPOSITION OF BLUE PIGMENT ON CHINESE BLUE‐AND‐WHITE PORCELAIN OF THE YUAN AND MING DYNASTIES (ad 1271–1644)*

Abstract: The chemical compositions of the glazes and pigments of 39 blue-and-white porcelains of Ming Dynasty date and three of Yuan date were examined by SR-XRF. Both the analysis of the Fe/Mn ratio in the light blue areas of the glaze and a comparison of the Fe/Mn values between light blue, dark blue and clear glaze areas reveals that the samples can be divided into three groups. The results indicate that there are two significant changes of provenance of blue pigment during the Ming Dynasty and that some kinds of pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 2 publications
(4 reference statements)
5
64
0
Order By: Relevance
“…; Wen et al . ). The imported blue pigment was recorded as sumali 苏麻离 blue, suboni 苏勃泥 blue and sumani 苏麻尼 blue, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Wen et al . ). The imported blue pigment was recorded as sumali 苏麻离 blue, suboni 苏勃泥 blue and sumani 苏麻尼 blue, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…However, the Yuan and early Ming samples present different iron and manganese distribution patterns compared with late Chinese blue‐and‐white porcelain, but are close to the Islamic samples (Wen et al . ; Wen and Pollard ). Chen Yao‐cheng and his colleagues have reported that the blue of the Yuan dynasty blue‐and‐white porcelain contained high iron and low manganese, and bears some arsenic and sulphur.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The resolution was 137.5 eV at Mn–K α and the dead time was near 30%. The software for spectrum retraction and analysis was VISION32, supplied with the instrument, and 13 pieces of ceramic standard samples provided by the Shanghai Institute of Ceramics of the Chinese Academy of Science (SICCAS), which were usually employed for determinations on the ancient ceramic materials, including the body and the high‐temperature glaze (Wu et al ; Wen et al ), were used for quantitative analysis as well. The analytical procedures used for this study have been recorded in a previous study (Zhu et al ) and the results for the elements Na, Mg, Al, Si, K, Ca, Ti, Fe, Co, Mn, Cu, Ni, Rb, Sr, Y and Zr are listed in Tables below.…”
Section: Methodsmentioning
confidence: 99%
“…Since the 1950s, many analytical instruments, including electron microprobe analysis (EMPA) (Guo and Qian ), micro X‐ray fluorescence spectrometry (μ‐XRF) (Wu et al ), synchrotron radiation X‐ray fluorescence spectrometry (SRXRF) (Wen et al ), particle‐induced X‐ray emission spectrometry (PIXE) (Cheng and Zhang ), X‐ray absorption fine structure spectroscopy (XAFS) (Wang and Wang ) and so on, have been employed to study the provenance of cobalt material and the chromogenic mechanism of the blue decoration of the Yuan Qinghua produced in Jingdezhen. However, only the gaudy blue type has been focused on and discussed, while the other two types, which contain equally important information with regard to recovering the manufacturing technology of Yuan Qinghua, have always been ignored by scientific researchers.…”
Section: Introductionmentioning
confidence: 99%